Pemikiran Ulama Tafsir Kontemporer tentang Objek Zakat dan Relevansinya terhadap Praktik di BAZNAS Kabupaten Mandailing Natal - Rukiah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Zakat is an important instrument in Islam that functions as a means of wealth distribution and community economic empowerment. The development of the modern economy has given rise to various new forms of wealth, encouraging the emergence of contemporary zakat thought, including that of Yusuf al-Qardhawi and Buya Hamka. This study aims to analyze the views of both scholars on zakat objects and examine their relevance to zakat management practices at BAZNAS Mandailing Natal Regency. The research employed a qualitative approach with a field research design. Primary data were collected through interviews and documentation, while secondary data were obtained from classical works, books, scholarly articles, and relevant official documents. Data were analyzed descriptively and comparatively. The findings reveal that Yusuf al-Qardhawi's ideas are reflected in zakat collection practices through the recognition of professional income zakat, the utilization of banking systems, and institutional zakat management. Meanwhile, Buya Hamka's thought is reflected in zakat distribution practices that emphasize social justice, solidarity, and public welfare through educational, health, socio-religious, and economic empowerment programs. Nevertheless, zakat distribution at BAZNAS Mandailing Natal Regency remains predominantly consumptive in nature, although efforts have been made to promote productive programs aimed at enhancing the self-reliance of beneficiaries (mustahik).